A Titanium Metal–Organic Framework with Visible‐Light‐Responsive Photocatalytic Activity. (27th May 2020) - Cadiau, Amandine; Kolobov, Nikita; Srinivasan, Sivaranjani; Goesten, Maarten G.; Haspel, Henrik; Bavykina, Anastasiya V.; Tchalala, Mohamed R.; Maity, Partha; Goryachev, Andrey; Poryvaev, Artem S.; Eddaoudi, Mohamed; Fedin, Matvey V.; et al.
Abstract: The one‐step synthesis and characterization of a new and robust titanium‐based metal–organic framework, ACM‐1, is reported. In this structure, which is based on infinite Ti−O chains and 4, 4′, 4′′, 4′′′‐(pyrene‐1, 3, 6, 8‐tetrayl) tetrabenzoic acid as a photosensitizer ligand, the combination of highly mobile photogenerated electrons and a strong hole localization at the organic linker results in large charge‐separation lifetimes. The suitable energies for band gap and conduction band minimum (CBM) offer great potential for a wide range of photocatalytic reactions, from hydrogen evolution to the selective oxidation of organic substrates. Abstract : A new metal–organic framework (MOF), based on infinite Ti−O chains and 4, 4′, 4′′, 4′′′‐(pyrene‐1, 3, 6, 8‐tetrayl)tetrabenzoic acid, shows great promise for a wide range of photocatalytic reactions, from hydrogen evolution to the selective oxidation of organic substrates.